Rapeseed Supports Hairy Vetch in Intercropping, Enhancing Root and Stem Morphology, Nitrogen Metabolism, Photosynthesis, and Forage Yield - Jianli Ji; Zongkai Wang; Pan Gao; Xiaoqiang Tan; Xianling Wang; Jie Kuai; Jing Wang; Zhenghua Xu; Bo Wang; Guangsheng Zhou; Jie Zhao (Agronomy)
The global shortage of high-quality forage has significantly constrained the development of animal husbandry. Leveraging the complementary effects of forage rapeseed and hairy vetch intercropping can enhance forage yield and quality; however, the underlying mechanisms of overyielding in forage rapeseed–hairy vetch intercropping systems remain unclear. Over two years of field experiments, three cropping systems—rapeseed sole cropping, hairy vetch sole cropping, and rapeseed–hairy vetch intercropping—were investigated to assess the effects of intercropping on root and stem morphology, canopy light distribution, leaf photosynthetic physiology, and nitrogen metabolism. Our results demonstrated that intercropping increased forage biomass and crude protein yield by 14.3–20.0% and 30.7–92.8%, respectively, compared to sole cropping. Intercropping significantly enhanced root biomass, increasing lateral root biomass by 81% compared to rapeseed sole cropping. It also improved stem anatomical traits, including the cortex area (58.8–80.7%), cortex thickness (25.1–38.3%), number of vascular bundles (18.0–37.3%), vascular bundle length (17.8–18.4%), vascular bundle perimeter (6.7–18.7%), vascular bundle area (34.6–63.9%), and stem breaking strength (25.7–76.6%). Additionally, intercropping optimized vertical canopy light interception, reduced the activity of antioxidant enzymes (CAT, POD, SOD) and reactive oxygen species (ROS) accumulation, and enhanced the activities of glutamine synthetase and nitrate reductase, stomatal traits, and photosynthetic rates in the leaves of both crops. Structural equation modeling revealed that, in the intercropping system, improved population lodging resistance directly promoted nitrogen metabolism and leaf photosynthetic rates, ultimately increasing population biomass. In summary, rapeseed–hairy vetch intercropping improved canopy light distribution, strengthened rapeseed stem anatomy and root penetration, and enhanced population lodging resistance, leaf photosynthetic physiology, and nitrogen metabolism, thereby boosting forage biomass and quality. The supportive role of rapeseed in the intercropping system elucidates the overyielding mechanisms of rapeseed–hairy vetch intercropping, offering a theoretical framework for optimizing forage production systems worldwide.